Solving BJT Circuits by Nodal Voltage Method with Application of Diakoptical Method - Brtník, Bohumil; Matoušek, David (IEEE (Institute of Electrical and Electronics Engineers), 2016)
Bipolar transistor circuits are usually solved by their h-parameters description. However, for circuit solutions are commonly used Nodal Voltage Method based on the y-parameters. Therefore it is necessary to convert these h-parameters (hybrid parameters) to y-parameters (admittance parameters) firstly. After then the circuit is solved by hand. But the conversion of parameters is not required when diakoptical method is used. Thus this way of circuit solution is explained in this paper.
Ŕešení obvodů s bipolárními tranzistory metodou uzlových napětí s použitím diakoptické metody
Keywords: diakoptical method; h-parameters; solving electronic circuits by hand; matrix method